Bronchial epithelial cells of patients with asthma release chemoattractant factors for T lymphocytes - Bellini, Alberto; Yoshimura, Hiroshi; Vittori, Enza; Marini, Maurizio; Mattoli, Sabrina (Journal of allergy and clinical immunology, 1993)
Background: T lymphocytes may orchestrate the inflammatory response in atopic asthma, but the mechanisms that promote T-cell accumulation in asthmatic airways are still unclear. In this study, we tested the hypothesis that bronchial epithelial cells of patients with atopic asthma release chemoattractant factors for T lymphocytes. Methods: Sixteen patients with atopic asthma and eight healthy control subjects were selected for this study. Bronchial epithelial cells were isolated from biopsy specimens obtained by means of bronchoscopy and cultured for 48 hours in serum- and hormone-free medium, with or without 10 −6 mol/L histamine. Results: Only the supernatants of cells from donors with asthma showed chemotactic activity for T lymphocytes, and this was significantly increased ( p < 0.025) by exposure to histamine. Chemotactic activity was in part mediated by interkukin-8 (IL-8), because an antibody against human IL-8 significantly reduced it ( p < 0.05) and the cell supematants contained appreciable amounts of immunoreactive IL-8 (0.89 ± 0.39 ng/ml). Both the residual chemotactic activity of unstimulated epithelial cells and the increased activity caused by histamine were mediated by a single protease-sensitive substance with an apparent molecular weight of 56,000 d and an extimated isoelectric point of 8.8 to 9.1. The partially purified chemoattractant specifically enhanced the migration of CD4+ T lymphocytes, and its activity was inhibited by the univalent Fab fragment of a monoclonal antibody against CD4. Conclusion: These results extend our previous observations, indicating an important effector role of bronchial epithelium in asthma.